FACTORS ASSOCIATED WITH WORK STRESS LEVEL AMONG HEALTHCARE PROFESSIONALS DURING CORONAVIRUS DISEASE 2019 - Chahyanto, Bibi Ahmad; Nasution, Herlina; Tiurlan, Mestika (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: The novel Coronavirus Disease 2019 pandemic has had negative impact on healthcare professionals, such as the risk of stress due to pressure during pandemic and they were afraid of bringing the virus to their home. Purpose: To analyze factors associated with work stress level among healthcare professionals during Coronavirus Disease 2019 pandemic. Method: Survey with cross sectional design was conducted in July 2020. Data was online collected using the Google Forms platform was distributed to healthcare professionals throughout the Public Health Center in Sibolga City. The total of healthcare professionals who met the inclusion criteria and became the sample was 233 people. The data was presented as result of descriptive and analytical analysis using Chi-Square and Spearman test to see the relationship between independent and dependent variable. Result: The sampel was dominated by adults as much as 87.55%. The male was 12.02% and female was 87.98%. As many as 63.52% of healthcare professionals was low stress level, moderate stress level 23.18, and severe stress level 13.30%. Statistical analysis between showed that only the age (p-value = 0.03) and the history of Coronavirus Disease 2019 patients contact (p-value = 0.04) was significantly associated with stress levels. Conclusion: The age of healthcare professionals and the history of Coronavirus Disease 2019 patients contact significantly related to stress level of healthcare professionals in the Public Health Center during the Coronavirus Disease 2019 pandemic.